Suppression of Xo1-Mediated Disease Resistance in Rice by a Truncated, Non-DNA-Binding TAL Effector of Xanthomonas oryzae - Read, Andrew C.; Rinaldi, Fabio C.; Hutin, Mathilde; He, Yong-Qiang; Triplett, Lindsay R.; Bogdanove, Adam J. (Frontiers in Plant Science, 2016)
Delivered into plant cells by type III secretion from pathogenic Xanthomonas species, TAL (transcription activator-like) effectors are nuclear-localized, DNA-binding proteins that directly activate specific host genes. Targets include genes important for disease, genes that confer resistance, and genes inconsequential to the host-pathogen interaction. TAL effector specificity is encoded by polymorphic repeats of 33-35 amino acids that interact one-to-one with nucleotides in the recognition site. Activity depends also on N-terminal sequences important for DNA binding and C-terminal nuclear localization signals (NLS) and an acidic activation domain (AD). Coding sequences missing much of the N- and C-terminal regions due to conserved, in-frame deletions are present and annotated as pseudogenes in sequenced strains of X. oryzae pv. oryzicola (Xoc) and pv. oryzae (Xoo), which cause bacterial leaf streak and bacterial blight of rice, respectively. Here we provide evidence that these sequences encode proteins we call ‘truncTALEs,’ for ‘truncated TAL effectors.’ We show that truncTALE Tal2h of Xoc strain BLS256, and by correlation truncTALEs in other strains, specifically suppress resistance mediated by the Xo1 locus recently described in the heirloom rice variety Carolina Gold. Xo1-mediated resistance is triggered by different TAL effectors from diverse X. oryzae strains, irrespective of their DNA binding specificity, and does not require the AD. This implies a direct protein-protein rather than protein-DNA interaction. Similarly, truncTALEs exhibit diverse predicted DNA recognition specificities. And, in vitro, Tal2h did not bind any of several potential recognition sites. Further, a single candidate NLS sequence in Tal2h was dispensable for resistance suppression. Many truncTALEs have one 28 aa repeat, a length not observed previously. Tested in an engineered TAL effector, this repeat required a single base pair deletion in the DNA, suggesting that it or a neighbor disengages. The presence of the 28 aa repeat, however, was not required for resistance suppression. TruncTALEs expand the paradigm for TAL effector-mediated effects on plants. We propose that Tal2h and other truncTALEs act as dominant negative ligands for an immune receptor encoded by the Xo1 locus, likely a nucleotide binding, leucine-rich repeat protein. Understanding truncTALE function and distribution will inform strategies for disease control.